Influence of visual and haptic cues on motor learning: Insights from tennis skill acquisition in children - Herbaut, A.; Valgalier, A.; Foissac, M.; McGann, J.; Issartel, J. (Journal of Motor Behavior, 2023)
Underdevelopment of cognitive abilities in children, such as memory and attention, may make the use of verbal instructions difficult for learning new motor skills. The objective of this study was to evaluate whether visual and haptic cues which emphasize certain instructions facilitate skill acquisition in young tennis players. Twenty children were distributed in 2 groups: experimental (EXP) and control (CON). EXP received a racket with visual and haptic cues while CON trained with a classic racket. The task consisted of playing 30 consecutive forehands during a pretest and 16 weeks post-intervention. EXP displayed a larger improvement both in their technique (better ready position, more balls hit in front and to the side of the body) and in their performance (more points scored), highlighting the positive impact of visual and haptic cues during the early stage of motor learning.